Novel Expression of EGFL7 in Osteosarcoma and Sensitivity to Cisplatin - Liu, Qing; He, Hongbo; Yuan, Yuhao; Zeng, Hao; Wang, Zhiwei; Luo, Wei (Frontiers in Oncology, 2020)
Epidermal growth factor-like domain 7 (EGFL7) is a protein specifically secreted by blood vessel endothelial cells, which plays an important role in angiogenesis. Considering the aberrant secretion of EGFL7 in osteosarcoma (OS) has not yet been elucidated, this study investigated the secretion of EGFL7 in OS and the changes in its secretion after chemotherapy. We observed increased varying secretion of EGFL7 in OS tissues compared with CS tissues. OS cell lines and HUVECs showed higher EGFL7 mRNA and protein expression than SW1353, with OS cells expressing the highest levels. In patient samples, EGFL7 was highly expressed in the cytoplasm of OS tumor cells and vascular endothelium cells. This overexpression was abolished in OS cell and tumor tissues when treated with chemotherapy. This study is a pioneering study to investigate EGFL7 expression and localization in human OS tissues and cell. Overexpression of EGFL-7 in response to chemotherapy suggests that it can be used as a therapeutic target for OS.